The Evolution of Behavior Analysis: Toward a Replication Crisis? - Locey, Matthew L. (Perspectives on behavior science, 2020)
The Open Science Collaboration ( Science, 349 (6251), 1–8, 2015 ) produced a massive failure to replicate previous research in psychology—what has been called a “replication crisis in psychology.” An important question for behavior scientists is: To what extent is behavior science vulnerable to this type of massive replication failure? That question is addressed by considering the features of a traditional approach to behavior science. Behavior science in its infancy was a natural science, inductive, within-subject approach that encouraged both direct and systematic replication. Each of these features of behavior science increased its resistance to three factors identified as responsible for the alleged replication crisis: (1) failures to replicate procedures, (2) low-power designs, and (3) publication bias toward positive results. As behavior science has evolved, the features of the traditional approach have become less ubiquitous. And if the science continues to evolve as it has, it will likely become more vulnerable to a massive replication failure like that reported by the Open Science Collaboration ( Science, 349 (6251), 1–8, 2015 ).